Desarrollo de una aplicación web y móvil empleando prácticas ágiles para la gestión de los productos y servicios de la lavadora de vehículos “Big Car” ubicada en la ciudad de Quito - Casa Yanguicela, Jessica Alexandra (2022)
This technological proposal was carried out in the province of Pichincha in the city of Quito, in which the problem was evidenced: the lack of a digital platform to keep track of the services and products offered by the "Big Car" vehicle washer. , where the processes of said management were carried out manually, causing a great loss of time for both clients and the business owner. For the development of the project, the types of research were used: Bibliographic, Descriptive, Mixed, Quantitative and Field, the techniques and instruments of data collection (survey and interview), in order to identify the main needs, in order to develop the project. applying software tools such as the Django Framework, the Python Language, JavaScript, PostgreSQL, Java, in the same way the agile Scrum methodology was applied for the web environment and the Mobile-D methodology for the mobile environment and the UML modeling language for the design of the respective diagrams. Obtaining as a result the implementation of the web and mobile application in the vehicle washer, highlighting the functionality of providing information on the prices of the products, being able to schedule a shift according to the time available by the client, managing to properly optimize resources such as time and investment to improve the management of the washing machine.